Consumer stated preferences for dairy products with carbon footprint labels in Italy - Maurizio Canavari; Silvia Coderoni (Agricultural and Food Economics, 2020)
Carbon footprint (CF) labels on agri-food products represent one of the most important tools to convey information to consumers about the greenhouse gases emissions associated with their purchase behaviour.
Keywords: D12; Q54; Q01; 330; Carbon footprint label; Environmental labels; Willingness to pay; Consumer preferences; Dairy products; Logistic regression